Answers

Solutions by everydaycalculation.com

Everydaycalculation.com » Answers » Solve for x

Solve 5x - 11 = 3x + 9

How to solve 5x - 11 = 3x + 9? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.

Steps for finding the solution

We have 5x - 11 = 3x + 9

First, we move the x terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:
i) Adding 11 to both sides
ii) Subtracting 3x from both sides

Therefore, 5x - 3x = 9 + 11

or, 2x = 20

Next, divide both sides by 2, which is the coefficent of x

Note: if a = b, then a ÷ c = b ÷ c

2x/2 = 20/2

x = 20/2

To simplify, divide both numerator and denominator by 2, which is the GCF of 20 and 2:

x = 10/1 or, x = 10

Solve another equation

𝒙 =

Related

© everydaycalculation.com